Risk patterns preceding diagnosis among newly HIV-diagnosed men who have sex with men in New York City. - Drabkin, Anya S; Sikkema, Kathleen J; Wilson, Patrick A; Meade, Christina S; Hansen, Nathan B; Delorenzo, Allyson; Kochman, Arlene; MacFarlane, Jessica C; Watt, Melissa H; Aunon, Frances M; Ranby, Krista W; Mayer, Gal (AIDS patient care and STDs, 2013)
Men who have sex with men (MSM) are at high risk for contracting and transmitting HIV. They are increasingly encouraged to get tested, but understanding of the interplay between HIV testing and risk behavior is limited. One hundred fifty newly HIV-diagnosed (within past 3 months) MSM were recruited from a community clinic in New York City. Participants completed an interview assessing sexual behavior and substance use during the 3 months pre-diagnosis, current depressive symptoms, and prior HIV testing. HIV-related health characteristics at diagnosis were abstracted from medical records. Analyses examined factors associated with unprotected anal intercourse (UAI) in the 3 months pre-diagnosis, and with a negative HIV test in the 12 months pre-diagnosis. The sample was young (mean age=32.5, SD=8.8), ethnically diverse (62% racial/ethnic minority), low-income (71%≤$30,000/year), and educated (48% college/advanced degree). Most (95%) had a prior negative HIV test, 55% within the last 12 months. Significant risk behavior was reported, with 79% reporting UAI. UAI was associated with recent testing and use of substances during sexual behavior. Recent testing was associated with being employed/a student, having had UAI, and higher CD4 count. Implications for future research addressing perceived HIV risk, HIV testing utilization, and risk behavior are discussed.
Keywords: Adult; CD4 Lymphocyte Count; Condoms; Health Behavior; HIV Infections; Homosexuality, Male; Humans; Interviews as Topic; Male; Mass Screening; New York City; Population Surveillance; Questionnaires; Risk Factors; Risk-Taking; Socioeconomic Factors; Substance-Related Disorders; Time Factors; Unsafe Sex; Viral Load; Young Adult